The Role of Blockchain Technology Transformation in Preventing and Detecting Financial Fraud as an Anti-Fraud System Revolution in Indonesia - Muhammad Syukeri; Faridah Faridah; M. Yulian Ma’mun; Faqih El Wafa (Institute of Advanced Knowledge and Science, 2026)
The high incidence of financial fraud in Indonesia, which exploits vulnerabilities in centralized record-keeping systems, has become a critical issue threatening economic stability. This study aims to analyze the role of blockchain technology transformation in preventing and detecting financial fraud as a revolution in the national anti-fraud system. This research employs a qualitative approach using a Systematic Literature Review (SLR), guided by the PRISMA protocol. Research data were extracted from 19 reputable international journal articles (Q1-Q3) indexed in Scopus, published between 2020 and 2024. The study concludes that blockchain is highly effective at eliminating manipulation loopholes through decentralization, absolute transparency, and data immutability, all of which are validated by algorithmic consensus and smart contracts. Although the research concludes that blockchain is superior as a future security system, it emphasizes that its implementation still faces challenges related to regulatory readiness, operational infrastructure adaptation, and network scalability limitations.